LIMBAH AMPAS TAHU SEBAGAI BAHAN BAKU SUMBER PROTEIN NABATI PAKAN IKAN NAGAN RAYA - Farah Diana; Ananingtyas Ananingtyas (Jurnal Marine Kreatif, 2018)
Nagan Raya is one of the districts on the west coast of Aceh with an area of 311,480 km2, consisting of 9 districts, 222 villages. The strategic location, the possibility of developing a large fishery field. Nagan Raya began to develop the field of fisheries through aquaculture. Devotion to this community using the method of mentoring and coaching through knowledge transfer in the form of training and practice of making fish feed into feed products. Process activities that have been implemented in the form of mentoring and coaching then classified the type of output at each stage that is passed; Partners can make artificial fish feed with waste alternatives using pellet machines, packing and marketing. Communities in Nagan Raya also produce tofu as processed from soybeans, this preparation will produce waste of tofu waste, which is currently not utilized optimally. The raw material of this training is the tofu and waste waste of dried fish to be processed into feed powder. Tofu waste is used as a feed ingredients because it has advantages in addition to the nutrient content owned also utilize waste processing so that environmental pollution can be avoided. Waste know this is an alternative material of raw materials of environmentally friendly fish feed. Because it is made from waste processing industry residue. Conceptually and the application of science transfer transfer is done through: aspects of fish feed manufacturing techniques and marketing aspects.